EFEKTIVITAS KEPUTUSAN MENTERI HUKUM DAN HAM TENTANG BESARAN BIAYA BANTUAN HUKUM LITIGASI DAN NON LITIGASI BAGI MASYARAKAT MISKIN - Indra Lesmana Poetra Salimuddin; Ibrahim Ahmad; Arifin Tumuhulawa (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2025)
This research aims to analyze the effectiveness of the implementation of the Decree of the Minister of Law and Human Rights M.HH-01.HN.03.03 of 2021 concerning the amount of legal aid fees for litigation and non-litigation for impoverished communities. Employing a socio-legal (yuridis empiris) approach, this study examines the prevailing legal provisions while also investigating actual legal events in society, with field research conducted in Gorontalo Province. The objective is to determine the extent to which this policy is effective in providing legal assistance to impoverished communities. The research findings indicate that although the Ministerial Decree has provided a crucial legal basis for the provision of legal aid, its implementation has not yet reached an optimal level from a technical execution perspective. Various obstacles were encountered in the field, including a mismatch between the stipulated fee amounts and the actual operational needs of legal aid provider organizations. This potentially hinders the quality and scope of services that can be provided to impoverished communities. To enhance the effectiveness of this policy, this research proposes several optimization strategies. These strategies include the necessity of periodically revising the amount of legal aid fees, taking into account factors such as inflation rates and the complexity of the cases handled. Furthermore, strengthening the capacity of legal aid institutions is essential, which can be achieved through continuous training for advocates and paralegals, the utilization of information technology to improve administrative and reporting efficiency, and the strengthening of collaborative networks among related institutions. A comparative study with other regions, such as DKI Jakarta, suggests that the adoption of administrative innovations and the utilization of digital technology have significant potential in increasing the efficiency and expanding the reach of legal aid services. Therefore, this research recommends several concrete steps: (1) Conducting periodic revisions of the legal aid fee amounts, considering economic conditions and the characteristics of the cases. (2) Encouraging local governments to allocate supporting budgets in the Regional Revenue and Expenditure Budget (APBD) to support the sustainability of legal aid programs at the local level. (3) Enhancing the institutional capacity of Legal Aid Organizations (OBH) through continuous training programs, the utilization of technology in operations, and the strengthening of collaboration with various relevant parties. With the comprehensive implementation of these optimization strategies, it is expected that legal aid programs can reach impoverished communities more effectively and contribute to the realization of the principle of social justice in Indonesia.